Limited miR-17-92 overexpression drives hematologic malignancies. Issue 3 (March 2015) - Danielson, Laura S.; Reavie, Linsey; Coussens, Marc; Davalos, Veronica; Castillo-Martin, Mireia; Guijarro, Maria V.; Coffre, Maryaline; Cordon-Cardo, Carlos; Aifantis, Iannis; Ibrahim, Sherif; Liu, Cynthia; Koralov, Sergei B.; et al.
Highlights Developed model with limited miR-17-92 overexpression across hematopoietic lineages. miR-17-92 expression is sufficient to drive B cell malignancies. SM22α-cre mediated recombination occurs in virtually all hematopoietic lineages.